Factor Structure and Invariance of a German Adaptation of the Primary Levenson Self-Report Psychopathy Scale - Deniz Cengiz Dericioğlu; Florian Schiller; Florian Schmitz (Psychological Test Adaptation and Development)
Abstract: This study was conducted to test the psychometric properties of a German adaptation of the Primary Levenson Self-Report Psychopathy Scale (LSRP). A large community sample (N = 1,040) was collected and divided into two parallel subsamples. One was used to explore the latent structure with a hierarchical cluster analysis, whereas the other subsample was used to test the structure with confirmatory factor analyses. A solution comprising two correlated factors offered the best model fit. The allocation of the three Machiavellianism items to the two factors differed from that found in previous studies and suggested an interpretation of the factors as egocentricity and deceitfulness. This revised measurement model with the refined item allocation possessed superior fit and reliability compared to one-factor and two-factor models that have previously been proposed for the Primary LSRP. Furthermore, the revised measurement model proved to be measurement invariant across male and female participants.